The effect of condensed tannins from Acacia mearnsii on in vitro kinetic parameters and feedlot lamb growth and carcass parameters - Featherstone, Bradley William (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.